Reliability and Validity of a Self-paced Cardiopulmonary Exercise Test in Post-MI Patients - Jenkins, Lauren Ann; Mauger, Alexis; Fisher, Jane; Hopker, James (International Journal of Sports Medicine, 2017)
A self-paced peak oxygen uptake (V̇O2peak) test (SPV) has been shown to produce higher V̇O2peak values compared to standard cardiopulmonary exercise tests (sCPET), but has not been tested on any clinical population. This study aimed to assess the reliability of the SPV in a healthy population (study 1), and the validity and reliability of the SPV in post-myocardial infarction (post-MI) patients (study 2). For study 1, 25 healthy participants completed 3 SPV’s. For study 2, 28 post-MI patients completed one sCPET and 2 SPV’s. The SPV consisted of 5×2-min stages where participants were able to self-regulate their effort by using incremental ‘clamps’ in ratings of perceived exertion. The sCPET consisted of a 20 W/min ramp. Results demonstrated the SPV to have a coefficient of variation for V̇O2peak of 4.7% for the healthy population, and 8.2% for the post-MI patients. Limits of agreement ranged between±4.22–5.86 ml·kg−1·min−1, with the intraclass correlation coefficient ranging between 0.89–0.95. In study 2, there was a significantly higher V̇O2peak achieved in the SPV (23.07±4.90 ml·kg−1·min−1) against the sCPET (21.29±4.93 ml·kg−1·min−1). It is concluded that these results provide initial evidence that the SPV may be a safe, valid and reliable method for determining exercise capacity in post-MI patients.
Keywords: cardiology; RPE; aerobic capacity; pacing